Urban-rural disparity of preventive healthcare utilisation among children under the universal health insurance coverage in Taiwan: a national birth cohort analysis. (May 2020) - Lu, C.L.; Hsu, Y.H.; Su, W.L.; Damayanti, N.A.; Chen, C.W.; Lin, Y.J.; Tsai, K.S.; Li, C.Y.
Abstract: Objective: In the context of universal health insurance coverage, this study aimed to determine whether urban–rural inequality still exists in preventive health care (PHC) amongst children in Taiwan. Study design: Prospective cohort study. Methods: A total of 184, 117 mothers and their children born in 2009 were identified as the study cohort. The number of children born in urban, satellite and rural areas was 40, 176, 57, 565 and 86, 805, respectively. All children were followed for 7 years, before which a total of seven times PHC were provided by Taiwan's National Health Insurance (NHI) programme. Ordinal logistic regression models were used to associate urbanisation level with the frequency of PHC utilisation. Stratified analyses were further performed in accordance with the children's birth weight and the mothers' birthplace. Results: Children from satellite areas had higher utilisation for the first four scheduled PHC visits. Children living in urban areas received more PHC for the fifth and sixth scheduled visits. Compared with those from rural areas, children in satellite areas exhibited a small but significant increase in odds in PHC utilisation, with a covariate-adjusted odds ratio (aOR) of 1.04 and 95% confidence interval (CI) of 1.02–1.06. By contrast, no significant difference was observed between rural and urban areas (aOR = 1.01). Further stratified analyses suggest more evident urban–rural difference in PHC utilisation amongst children with low birth weight and foreign-born mothers. Conclusions: Given a universal health insurance coverage and embedded mechanisms in increasing the availability of healthcare resources in Taiwan, a slight urban–rural difference is observed in PHC utilisation amongst children. Hence, sociodemographic inequality in utilisation of PHC still exists. This issue should be addressed through policy intervention. Highlights: Urban-rural disparity in children's preventive care utilisation in Taiwan is small. The universal health insurance coverage may help reduce the disparity. Preventive care utilisation is relatively low amongst low birth weight children. It is also low amongst children having foreign-born mothers. Regular monitoring of utilisation by policymakers is strongly recommended.